Prevalencia de hipertensión arterial en personas mayores de 18 años en un municipio de Cundinamarca en el año 2017 (2017)
The arterial hypertension is a vascular disorder of the organism where its main manifestation is given by the increase in blood pressure figures, being a public health disease among all the populations, for which it is decided to carry out a study in Caparrapí, Cundinamarca during 2017 given the different problems presented in this locality as lack of knowledge and education, inadequate attention to the health service, and the history of violence already known at the national level that fomented indifference to the region and its people, because of this it is decided to establish the prevalence of arterial hypertension in people older than 18 years who live within the jurisdiction of this municipality, performing this study by manually taking blood pressure and collecting data on the lifestyle of the same; being a cross-sectional study, the sample collected was 370 people, of whom 154 presented the disease giving a significant prevalence of 42%, and it is also worth mentioning that 66.23% of them are controlled and another 19.48% are not, besides that 14.29% presents the disease without a confirmed diagnosis, being of greater predominance in the rural area due to different current problems in social, economic and cultural level, also the different risk factors associated with the disease as age, monthly income, consumption of tobacco and alcohol, consumption of fruits, vegetables, oils, and physical activity, all described throughout this document and that allows us to determine the deficiencies that occur in Caparrapí population as to styles suitable for their quality of life.